Haploproduction capacity of bread winter wheat genotypes in the presence of wheat-rye translocation in the genotype - Шестопал, О. Л.; Замбріборщ, І. С.; Топал, М. М. (The Journal of V.N.Karazin Kharkiv National University. Series «Biology», 2014)
The ability of response to androgenesis of 11 genotypes of bread winter wheat, which differ by the presence of wheat-rye translocations 1BL/1RS, 1BL/1RSm (modification) and 1AL/1RS were studied. Differences between the indices of androgenesis (as "induction of embryoides" and "regeneration of green plants") in these groups of genotypes were detected. It was shown that translocations 1BL/1RS, 1BL/1RSm in genotype of bread winter wheat increase ability to haploid production  in anther culture in vitro.